Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Pédagogie des opprimés suivi de Conscientisation et révolution - Freire, Paulo (Petite collection Maspero, 1974)
Ouvrage majeur de Paulo Freire, ce livre présente quelques aspects d’une pédagogie élaborée non seulement pour les opprimés, mais avec eux, et dans le cadre même de leur lutte perpétuelle pour affirmer leur humanité.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem7000; histoire et politique; inégalités; justice sociale; militance; pédagogie; ressource en ligne; systèmes d'oppressions; thématiques; éducation

Un groupe de femmes de Montréal - Un groupe de femmes québécoises. (Manifeste des femmes québécoises, 1971)
Keywords: 1900-1999; 1970-1979; EDI; amériques; approches et analyses; conflit; cours; fem1000; groupes communautaires; histoire et politique; justice sociale; militance; mouvements féministes; premier cycle; périodes historiques; québec; régions géographiques; thématiques